Factors influencing innovation and entrepreneur self-efficacy: A lifestyle entrepreneurship analysis - Cascais, Eduardo Maria Fonseca (2021)
Lifestyle entrepreneurs are generally associated with tourism firms and good quality of life. Given the importance of this group of individuals to the positive contribution of local destination and job creation this dissertation explored the key factors influencing Innovation and entrepreneurial Self-Efficacy (ESE) in Lifestyle entrepreneurs. The researcher conducted a quantitative study through a survey of 115 Lifestyle Entrepreneurs, to analyze the relationship between 5 concepts: (I) Innovation, (II) Marshalling, (III) Place Familiarity Perception, (IV) Communication and (V) Entrepreneurial Self-Efficacy (ESE). The target population of this study was lifestyle entrepreneurs from Portugal and Spain who state in the survey, as a motive for their business, non-financial reasons or non-financial reasons and financial reasons. After collecting and analyzing the data, it was established several direct and one indirect relationship between variables. The results indicate that marshalling has a significantly positive and direct effect on both ESE and communication. Communication has a direct and positive relationship on innovation. Place familiarity perception has a significantly positive and direct relation on communication and innovation on ESE. It was also found that there isn’t a direct but rather, an indirect link between these marshalling and innovation via the mediator communication.